Signs monitoring ion conductive fabric and preparation method thereof

By combining No. 1 and No. 2 polyacrylonitrile and combining multi-walled carbon nanotubes with silver nanowires and copper particles, and combining them with ionic liquid crosslinking agents to form a conductive network, the problem of insufficient comprehensive performance of conductive fabrics in vital sign monitoring is solved. High conductivity, excellent tensile strength and suitable moisture regain are achieved, which improves signal acquisition and wearing comfort.

CN123043706APending Publication Date: 2026-11-06JIANGSU DEBAI INTELLIGENT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610891854.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing conductive fabrics have difficulty achieving synergistic improvements in comprehensive properties such as conductivity, tensile strength, elongation at break, and moisture regain, resulting in inaccurate signal acquisition, poor comfort, and easy damage to sensors in vital sign monitoring scenarios.

Method used

A multidimensional conductive network was formed by compounding polyacrylonitrile No. 1 and No. 2, carboxylating, amifying, and hydroxylating multi-walled carbon nanotubes, silver nanowires, and copper nanoparticles. In the ion-conductive finishing solution, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ionic liquid and aziridine crosslinking agent were introduced to form a hydrophilic three-dimensional network structure.

Benefits of technology

The fabric's electrical conductivity, tensile strength, and elongation at break were improved, while its moisture regain was increased, achieving high-sensitivity signal acquisition in vital sign monitoring and long-term wear comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention belongs to the field of conductive fabric technology, specifically relating to an ion-conductive fabric for vital sign monitoring and its preparation method. The preparation method includes the following steps: (1) preparation of spinning solution; (2) preparation of carbon nanotube dispersion; (3) preparation of composite conductive filler; (4) compounding of ion-conductive finishing solution; (5) electrospinning; and (6) thermal crosslinking and setting. The preparation method provided by this invention can solve the problem that existing conductive fabrics are difficult to improve in terms of comprehensive performance such as conductivity, tensile strength, elongation at break, and moisture regain. The fabric obtained has high conductivity, excellent tensile strength and elongation at break, as well as comfortable moisture regain, and is suitable for long-term wear in vital sign monitoring scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of conductive fabric technology, specifically relating to an ion-conductive fabric for vital sign monitoring and its preparation method. Background Technology

[0002] In recent years, with the rapid development of mobile internet, IoT, and AI technologies, wearable electronic devices have shown tremendous market potential in fields such as medical health monitoring, sports training, and human-computer interaction. As the core interface for direct interaction between wearable devices and the human body, the performance of flexible sensors directly determines the accuracy of signal acquisition, the comfort of the device, and its long-term reliability. Among these, flexible sensors based on conductive fabrics have become an ideal alternative to traditional rigid sensors due to their excellent breathability, softness, and wearability. Conductive fabrics, by combining conductive components (such as metal nanomaterials, carbon-based materials, and conductive polymers) with textile fibers, retain the inherent properties of the fabric while endowing it with conductive functionality, enabling real-time monitoring of physiological signals such as electrocardiograms, electromyograms, pulse, respiration, and joint movements.

[0003] Chinese patent CN113096850B discloses a highly conductive fabric based on graphene conductive paste and its coating process. The highly conductive fabric prepared by this invention can be applied to the field of flexible sensor technology, and the resulting flexible sensor has high sensitivity and repeatable stability. Chinese patent CN110656391B discloses a composite conductive fabric and its manufacturing method. The composite conductive fabric prepared by this invention has excellent electrical conductivity and good tensile strength.

[0004] However, the aforementioned existing technologies still have the following shortcomings when practically applied to vital sign monitoring scenarios: First, conductivity and tensile strength still need further improvement. For wearable vital sign monitoring devices, conductivity directly determines the sensitivity and signal-to-noise ratio of the sensor in acquiring physiological signals. When conductivity is too low, weak human physiological signals are easily drowned out by environmental noise, leading to signal distortion or inability to be recognized. Especially in dynamic monitoring scenarios, the fabric needs to withstand repeated stretching, bending, and friction. If the tensile strength is insufficient, the conductive network is prone to irreversible damage, causing sensor failure. Elongation at break, as a core indicator of material flexibility, determines whether the conductive fabric can conform to human skin and deform without cracking. Skin deformation occurs during daily activities. If the elongation at break of the fabric is too low, it will cause the sensor to break or the signal to change abruptly during wear.

[0005] Secondly, current technologies do not pay enough attention to moisture regain, an indicator crucial for long-term wear comfort and signal stability. Moisture regain refers to the percentage of water weight in a textile material under standard atmospheric conditions relative to its dry weight. Moisture regain can significantly improve wearing comfort; high moisture regain fabrics can actively absorb and conduct sweat from the skin's surface, preventing the buildup of liquid water film that causes stuffiness and stickiness, and keeping the skin dry. However, the moisture regain of existing fabrics is generally low, indicating a significant lack of systematic optimization for wearing comfort.

[0006] In summary, existing conductive fabric technologies still have room for synergistic improvement in terms of overall performance, such as conductivity, tensile strength, elongation at break, and moisture regain. Summary of the Invention

[0007] The purpose of this invention is to provide an ion-conductive fabric for vital sign monitoring and its preparation method, thereby solving the problem that existing conductive fabrics are difficult to improve in a synergistic manner in terms of comprehensive performance such as conductivity, tensile strength, elongation at break, and moisture regain. The resulting fabric has high conductivity, excellent tensile strength and elongation at break, as well as suitable comfort and moisture regain. The conductivity of the conductive fabric is 4.6 × 10⁻⁶. -2 -7.4×10 -2 S / cm; tensile strength is 5.58-6.13cN / dtex; elongation at break is 44.1%-47.7%; moisture regain is 8.43%-9.31%, suitable for long-term wear for vital sign monitoring.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing an ion-conductive fabric for vital sign monitoring includes the following steps: (1) Preparation of spinning solution: Polyacrylonitrile is dissolved in dimethylformamide to prepare a polymer solution, and stirred to dissolve, thus obtaining a two-component polyacrylonitrile spinning solution; (2) Preparation of carbon nanotube dispersion: Carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes were mixed, added to deionized water, and a dispersant was added. The mixture was then ultrasonically dispersed to obtain a carbon nanotube dispersion. (3) Preparation of composite conductive filler: Mix silver nanowires and copper nanoparticles to obtain conductive metal particles; add the conductive metal particles to the carbon nanotube dispersion prepared in step (2), continue ultrasonic dispersion, then centrifuge, wash and freeze dry to obtain composite conductive filler; (4) Compounding of ion-conductive finishing solution: The composite conductive filler, ionic liquid, waterborne polyurethane and crosslinking agent obtained in step (3) are added to the solvent, stirred and ultrasonically dispersed to obtain the ion-conductive finishing solution. (5) Blending electrospinning: The spinning solution from step (1) is mixed with the ion-conducting finishing solution from step (4), and injected into an electrospinning device for blending spinning to obtain a composite nanofiber membrane. (6) Thermal cross-linking and shaping: The composite nanofiber membrane obtained in step (5) is vacuum dried and heat-treated to obtain an ion-conductive fabric for vital sign monitoring.

[0009] Preferably, the polyacrylonitrile includes polyacrylonitrile No. 1 and polyacrylonitrile No. 2; the average molecular weight Mw of polyacrylonitrile No. 1 is 80,000-90,000; and the average molecular weight Mw of polyacrylonitrile No. 2 is 140,000-160,000.

[0010] Preferably, the polyacrylonitrile comprises polyacrylonitrile No. 1 and polyacrylonitrile No. 2 in a mass ratio of 1:(0.3-0.5).

[0011] Preferably, the average molecular weight (Mw) of polyacrylonitrile No. 1 is 85,000.

[0012] Preferably, the average molecular weight (Mw) of polyacrylonitrile No. 2 is 150,000.

[0013] Existing conductive fabrics typically use a single molecular weight polyacrylonitrile (PAC) as the matrix, making it difficult to simultaneously achieve good tensile strength and elongation at break. This invention blends PAC1 and PAC2 in a specific mass ratio. The low molecular weight component provides good spinnability and flexibility, while the high molecular weight component imparts a fibrous skeletal structure to ensure strength, thus improving the fabric's tensile strength and elongation at break. Analysis shows that in the fiber network structure formed by the dual molecular weight blend, the high molecular weight segments bear the load transfer, while the low molecular weight segments fill defects and absorb deformation energy.

[0014] Preferably, the mass ratio of carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes is (45-55):(22-28):(22-28).

[0015] Preferably, the mass ratio of carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes in step (2) is 50:25:25.

[0016] In existing technologies, carbon nanotubes are prone to aggregation and have weak interfacial bonding with polymer matrices. Single-morphology conductive fillers struggle to form continuous conductive pathways, resulting in low fabric conductivity and significant conductivity degradation after stretching. This invention employs a blend of carboxylated, aminated, and hydroxylated multi-walled carbon nanotubes, along with the introduction of silver nanowires and copper nanoparticles, forming a multi-dimensional conductive network of carbon nanotube overlap, silver wire penetration, and copper particle filling. This improves the fabric's conductivity and tensile stability. Analysis indicates that the three functional groups synergistically inhibit carbon nanotube aggregation, while the silver wires and copper particles compensate for the contact resistance between carbon nanotubes.

[0017] Preferably, the dispersant is sodium dodecylbenzenesulfonate.

[0018] Preferably, the crosslinking agent is a aziridine crosslinking agent.

[0019] Preferably, the silver nanowires and copper nanoparticles are mixed at a mass ratio of (13-15):(5-7).

[0020] Preferably, the diameter of the silver nanowires is 35-45 nm and the length is 12-18 μm; the particle size of the copper nanoparticles is 30-50 nm.

[0021] Preferably, the diameter of the silver nanowire is 40 nm and the length is 15 μm; the particle size of the copper nanoparticles is 30-50 nm.

[0022] Preferably, the mass ratio of carbon nanotubes to conductive metal particles is (2-3):(1-1.5).

[0023] Preferably, the mass ratio of carbon nanotubes to conductive metal particles in step (3) is 2.5:1, wherein the mass ratio of silver nanowires to copper nanoparticles is 70:30.

[0024] Preferably, the mass ratio of the composite conductive filler, ionic liquid, waterborne polyurethane and crosslinking agent is (8-12):(12-18):(65-75):(2-4).

[0025] Preferably, the mass ratio of the composite conductive filler, ionic liquid, waterborne polyurethane and crosslinking agent in step (4) is 10:15:72:3.

[0026] Existing conductive fabrics often use hydrophobic polymer matrices, resulting in generally low moisture regain. This leads to prolonged wear causing stuffiness and discomfort, severe static electricity buildup, and unstable conductivity in ion-conductive media in the absence of moisture. This invention introduces 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ionic liquid into the ion-conductive finishing liquid, and simultaneously adds an aziridine crosslinking agent to react with waterborne polyurethane at room temperature, forming a more hydrophilic three-dimensional network structure. This improves the fabric's moisture regain and wearing comfort, while stabilizing the ionic conductivity. Analysis shows that the hydrophilic cations in the ionic liquid form hydrogen bonds with the carboxyl groups in the crosslinked network, endowing the fabric with active moisture-wicking capabilities.

[0027] Preferably, the spinning voltage in step (5) is 18kV, the receiving distance is 18cm, and the propulsion rate is 1.0mL / h.

[0028] Preferably, the heat treatment temperature in step (6) is 165°C and the time is 30 min.

[0029] This invention provides an ion-conductive fabric for vital sign monitoring prepared by the above-described method.

[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This invention blends No. 1 polyacrylonitrile and No. 2 polyacrylonitrile in a specific mass ratio. The low molecular weight component provides good spinnability and flexibility, while the high molecular weight component imparts a skeletal structure to the fiber to ensure strength, thus improving the tensile strength and elongation at break of the fabric. Analysis shows that in the fiber network structure formed by the dual molecular weight blend, the high molecular weight segments bear the load transfer, while the low molecular weight segments fill defects and absorb deformation energy.

[0031] 2. This invention uses a combination of three types of multi-walled carbon nanotubes: carboxylated, aminated, and hydroxylated, while introducing silver nanowires and copper nanoparticles to form a multi-dimensional conductive network of carbon nanotube overlap, silver wire penetration, and copper particle filling, thereby improving the electrical conductivity and tensile stability of the fabric.

[0032] 3. In this invention, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ionic liquid is introduced into the ionic conductive finishing liquid. At the same time, aziridine crosslinking agent is added to react with waterborne polyurethane at room temperature to form a more hydrophilic three-dimensional network structure, which improves the moisture regain and wearing comfort of the fabric, while stabilizing the ionic conductivity. Detailed Implementation

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] All raw materials used in the following embodiments of the present invention are commercially available products: Ionic liquid: 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, [EMIM]TFSI. Shanghai Aladdin Biochemical Technology Co., Ltd., item number E359386.

[0035] Waterborne polyurethane, solids content 35%. Juneng Chemical JNPUD-6413.

[0036] The crosslinking agent used is aziridine crosslinking agent, DSM CX-100.

[0037] The average molecular weight (Mw) of polyacrylonitrile No. 1 is 85,000. McLean, catalog number P823209.

[0038] The average molecular weight (Mw) of polyacrylonitrile No. 2 is 150,000. Maclean's, catalog number P823208.

[0039] Carboxylated polyacrylonitrile, with a carboxyl content of 5.0 mol% and a molecular weight of 85,000.

[0040] Carboxylated multi-walled carbon nanotubes: outer diameter 10-20 nm, length 10-30 μm.

[0041] Aminated multi-walled carbon nanotubes: outer diameter 10-20 nm, length 10-30 μm.

[0042] Hydroxylated multi-walled carbon nanotubes: outer diameter 10-20 nm, length 10-30 μm.

[0043] Example 1 This embodiment provides an ion-conductive fabric for vital sign monitoring, and the preparation method includes the following steps: (1) Preparation of spinning solution: Dissolve 10 parts by weight of polyacrylonitrile in 80 parts by weight of dimethylformamide, and stir in a water bath at 60°C for 4 hours until completely dissolved to obtain a transparent spinning solution. The polyacrylonitrile includes No. 1 polyacrylonitrile and No. 2 polyacrylonitrile in a mass ratio of 1:0.4; the average molecular weight Mw of No. 1 polyacrylonitrile is 85,000. The average molecular weight Mw of No. 2 polyacrylonitrile is 150,000.

[0044] (2) Preparation of carbon nanotube dispersion: 125 parts by weight of carboxylated multi-walled carbon nanotubes, 62.5 parts by weight of aminated multi-walled carbon nanotubes and 62.5 parts by weight of hydroxylated multi-walled carbon nanotubes were weighed and added to 250 parts by weight of deionized water. 2 parts by weight of sodium dodecylbenzenesulfonate were added and ultrasonically dispersed for 1.5 h to obtain carbon nanotube dispersion.

[0045] (3) Preparation of conductive particle composite filler: Take 70 parts by mass of silver nanowires and 30 parts by mass of copper nanoparticles, add them to the carbon nanotube dispersion prepared in step (2), continue ultrasonic dispersion for 30 min, then centrifuge at 10000 rpm for 15 min, wash three times with deionized water, and freeze dry for 24 h to obtain the composite conductive filler. Silver nanowires: diameter 40 nm, length 15 μm. Copper nanoparticles: particle size 30-50 nm.

[0046] (4) Formulation of ion-conductive finishing solution: Weigh 10 parts by weight of composite conductive filler, 15 parts by weight of ionic liquid, 205.7 parts by weight of waterborne polyurethane emulsion with a solid content of 35% (approximately 72 parts by weight on a dry basis), and 3 parts by weight of crosslinking agent. Add the above components to a DMF / water mixed solvent (85 parts by weight of DMF and 15 parts by weight of deionized water), stir at 1000 rpm for 1 hour, and then ultrasonically disperse for 30 minutes to obtain a uniform ion-conductive finishing solution.

[0047] (5) Blending electrospinning: The spinning solution from step (1) and the ion-conductive finishing solution from step (4) are mixed at a volume ratio of 4:1 and stirred for 30 minutes until homogeneous. The mixture is injected into the electrospinning apparatus. The spinning parameters are: voltage 18kV, receiving distance 18cm, feed rate 1.0mL / h, receiving drum speed 200rpm, ambient temperature 25℃, and relative humidity 40%. Spinning is carried out for 4 hours to obtain a composite nanofiber membrane.

[0048] (6) Thermal crosslinking and shaping: The nanofiber membrane obtained in step (5) is placed in a vacuum drying oven and dried at 80°C for 2 hours. Then it is transferred to an oven and heated to 165°C at 5°C / min in an air atmosphere. It is kept at the temperature for 30 minutes and then naturally cooled to room temperature to obtain the ion-conductive fabric for vital sign monitoring.

[0049] Example 2 This embodiment provides an ion-conductive fabric for vital sign monitoring, and the preparation method includes the following steps: (1) Preparation of spinning solution: Dissolve 10 parts by weight of polyacrylonitrile in 80 parts by weight of dimethylformamide, and stir in a water bath at 60°C for 4 hours until completely dissolved to obtain a transparent spinning solution. The polyacrylonitrile includes No. 1 polyacrylonitrile and No. 2 polyacrylonitrile in a mass ratio of 1:0.3; the average molecular weight Mw of No. 1 polyacrylonitrile is 85,000. The average molecular weight Mw of No. 2 polyacrylonitrile is 150,000.

[0050] (2) Preparation of carbon nanotube dispersion: 126.4 parts by weight of carboxylated multi-walled carbon nanotubes, 61.8 parts by weight of aminated multi-walled carbon nanotubes and 61.8 parts by weight of hydroxylated multi-walled carbon nanotubes were weighed and added to 250 parts by weight of deionized water. 2 parts by weight of sodium dodecylbenzenesulfonate were added and ultrasonically dispersed for 1.5 h to obtain carbon nanotube dispersion.

[0051] (3) Preparation of conductive particle composite filler: Weigh 90.3 parts by mass of silver nanowires and 34.7 parts by mass of copper nanoparticles, add them to the carbon nanotube dispersion prepared in step (2), continue ultrasonic dispersion for 30 min, then centrifuge at 10000 rpm for 15 min, wash three times with deionized water, and freeze dry for 24 h to obtain the composite conductive filler. Silver nanowires: diameter 40 nm, length 15 μm. Copper nanoparticles: particle size 30-50 nm.

[0052] (4) Formulation of ion-conductive finishing solution: Weigh 10 parts by weight of composite conductive filler, 15 parts by weight of ionic liquid, 205.7 parts by weight of waterborne polyurethane emulsion with a solid content of 35% (approximately 72 parts by weight on a dry basis), and 3 parts by weight of crosslinking agent. Add the above components to a DMF / water mixed solvent (85 parts by weight of DMF and 15 parts by weight of deionized water), stir at 1000 rpm for 1 hour, and then ultrasonically disperse for 30 minutes to obtain a uniform ion-conductive finishing solution.

[0053] (5) Blending electrospinning: The spinning solution from step (1) and the ion-conductive finishing solution from step (4) are mixed at a volume ratio of 4:1 and stirred for 30 minutes until homogeneous. The mixture is injected into the electrospinning apparatus. The spinning parameters are: voltage 18kV, receiving distance 18cm, feed rate 1.0mL / h, receiving drum speed 200rpm, ambient temperature 25℃, and relative humidity 40%. Spinning is carried out for 4 hours to obtain a composite nanofiber membrane.

[0054] (6) Thermal crosslinking and shaping: The nanofiber membrane obtained in step (5) is placed in a vacuum drying oven and dried at 80°C for 2 hours. Then it is transferred to an oven and heated to 165°C at 5°C / min in an air atmosphere. It is kept at the temperature for 30 minutes and then naturally cooled to room temperature to obtain the ion-conductive fabric for vital sign monitoring.

[0055] Example 3 This embodiment provides an ion-conductive fabric for vital sign monitoring, and the preparation method includes the following steps: (1) Preparation of spinning solution: Dissolve 10 parts by weight of polyacrylonitrile in 80 parts by weight of dimethylformamide, and stir in a water bath at 60°C for 4 hours until completely dissolved to obtain a transparent spinning solution. The polyacrylonitrile includes No. 1 polyacrylonitrile and No. 2 polyacrylonitrile in a mass ratio of 1:0.5; the average molecular weight Mw of No. 1 polyacrylonitrile is 85,000. The average molecular weight Mw of No. 2 polyacrylonitrile is 150,000.

[0056] (2) Preparation of carbon nanotube dispersion: 123.9 parts by weight of carboxylated multi-walled carbon nanotubes, 63.1 parts by weight of aminated multi-walled carbon nanotubes and 63.1 parts by weight of hydroxylated multi-walled carbon nanotubes were weighed and added to 250 parts by weight of deionized water. 2 parts by weight of sodium dodecylbenzenesulfonate were added and ultrasonically dispersed for 1.5 h to obtain carbon nanotube dispersion.

[0057] (3) Preparation of conductive particle composite filler: Weigh 56.8 parts by mass of silver nanowires and 26.5 parts by mass of copper nanoparticles, add them to the carbon nanotube dispersion prepared in step (2), continue ultrasonic dispersion for 30 min, then centrifuge at 10000 rpm for 15 min, wash three times with deionized water, and freeze dry for 24 h to obtain the composite conductive filler. Silver nanowires: diameter 40 nm, length 15 μm. Copper nanoparticles: particle size 30-50 nm.

[0058] (4) Formulation of ion-conductive finishing solution: Weigh 10 parts by weight of composite conductive filler, 15 parts by weight of ionic liquid, 205.7 parts by weight of waterborne polyurethane emulsion with a solid content of 35% (approximately 72 parts by weight on a dry basis), and 3 parts by weight of crosslinking agent. Add the above components to a DMF / water mixed solvent (85 parts by weight of DMF and 15 parts by weight of deionized water), stir at 1000 rpm for 1 hour, and then ultrasonically disperse for 30 minutes to obtain a uniform ion-conductive finishing solution.

[0059] (5) Blending electrospinning: The spinning solution from step (1) and the ion-conductive finishing solution from step (4) are mixed at a volume ratio of 4:1 and stirred for 30 minutes until homogeneous. The mixture is injected into the electrospinning apparatus. The spinning parameters are: voltage 18kV, receiving distance 18cm, feed rate 1.0mL / h, receiving drum speed 200rpm, ambient temperature 25℃, and relative humidity 40%. Spinning is carried out for 4 hours to obtain a composite nanofiber membrane.

[0060] (6) Thermal crosslinking and shaping: The nanofiber membrane obtained in step (5) is placed in a vacuum drying oven and dried at 80°C for 2 hours. Then it is transferred to an oven and heated to 165°C at 5°C / min in an air atmosphere. It is kept at the temperature for 30 minutes and then naturally cooled to room temperature to obtain the ion-conductive fabric for vital sign monitoring.

[0061] Comparative Example 1 The difference from Example 1 is that in step (1), only No. 1 polyacrylonitrile (Mw=85000) is used, and No. 2 polyacrylonitrile is not added, and the total mass is still 10 parts by mass.

[0062] Comparative Example 2 The difference from Example 1 is that in step (1), only No. 2 polyacrylonitrile (Mw=150000) is used, and No. 1 polyacrylonitrile is not added, and the total mass is still 10 parts by mass.

[0063] Comparative Example 3 The difference from Example 1 is that in step (2), only carboxylated multi-walled carbon nanotubes and aminated carbon nanotubes are used, totaling 250 parts by mass, with a mass ratio of 2:1 for carboxylated multi-walled carbon nanotubes and aminated multi-walled carbon nanotubes.

[0064] Comparative Example 4 The difference from Example 1 is that the mass ratio of carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes in step (2) is 1:1:1.

[0065] Comparative Example 5 The difference from Example 1 is that in step (3), 50 parts by mass of silver nanowires and 50 parts by mass of copper nanoparticles are added to the carbon nanotube dispersion prepared in step (2).

[0066] Comparative Example 6 The difference from Example 1 is that the diameter of the silver nanowire is 60 nm and the length is 25 μm; the particle size of the copper nanoparticles is 100-150 nm.

[0067] Comparative Example 7 The difference from Example 1 is that no ionic liquid is added in step (4), and the mass ratio of composite conductive filler, waterborne polyurethane and crosslinking agent is adjusted to 10:87:3, while keeping the total dry basis mass unchanged.

[0068] Comparative Example 8 The difference between this comparative example and Example 1 is that the composite conductive fabric prepared in Example 1 is based on Chinese Patent CN110656391B, which discloses a composite conductive fabric and its manufacturing method. It should be noted that the average molecular weight (Mw) of the polyacrylonitrile used in this comparative example is 85,000. (McLean, catalog number P823209).

[0069] Performance testing The fabrics prepared in Examples 1-3 and Comparative Examples 1-8 were subjected to performance tests: Electrical conductivity: GB / T45370-2025 "Determination of electrical conductivity of textile yarns" Tensile strength: EN ISO 5079:2020 "Textiles - Determination of breaking strength and elongation of individual fibers"; Elongation at break: EN ISO 5079:2020 "Textiles - Determination of breaking strength and elongation of single fiber"; Moisture regain: GB / T6503-2017 "Test Method for Moisture Regain of Chemical Fibers"; The test results are shown in Table 1.

[0070] Table 1 Performance Test Results

[0071] As shown in Table 1, the ion-conductive fabrics prepared in Examples 1-3 all exhibit excellent performance in terms of conductivity, tensile strength, elongation at break, and moisture regain, achieving a good balance in overall performance.

[0072] Comparative Example 1 used a single low-molecular-weight polyacrylonitrile (PMBN). The shorter molecular chains of the PMBN matrix weaken the coating and anchoring effect on the conductive filler. Some of the composite conductive filler easily detached from the fiber surface or agglomerated during spinning and thermal cross-linking, leading to a discontinuous conductive network and decreased conductivity. The lack of a long-chain skeleton supported by the high-molecular-weight component resulted in weak intermolecular forces within the fiber, making it prone to chain slippage under load and significantly reducing tensile strength. Although the low-molecular-weight component itself has decent flexibility, the lack of an entangled network of high-molecular-weight segments prevented the fiber from effectively dispersing stress during stretching, leading to premature breakage and reduced elongation at break. The relatively high nitrile content of the low-molecular-weight PIBN resulted in a decrease in moisture regain.

[0073] Comparative Example 2 used a single high-molecular-weight polyacrylonitrile (PMBN). The high PMBN resulted in excessively high solution viscosity, making it easy for conductive fillers to agglomerate locally. Simultaneously, the jet flow during spinning was unstable, resulting in a wide fiber diameter distribution, uneven conductive pathways, and decreased conductivity. Although the theoretical strength of the high-molecular-weight segments is high, poor spinnability during spinning easily leads to internal microcracks and structural defects, ultimately reducing the actual tensile strength. The fiber from a single high-molecular-weight component was excessively rigid and lacked toughness. While the molecular chain orientation was high, the lack of plasticizing effect from the low-molecular-weight component resulted in a reduced elongation at break. The high crystallinity of PMBN made it difficult for water molecules to enter the amorphous region, leading to a decrease in moisture regain.

[0074] Comparative Example 3, using only carboxylated and aminated carbon nanotubes, lacked the electrostatic repulsion and steric hindrance synergy of hydroxyl functional groups. This led to easy aggregation of carbon nanotubes in the matrix, impaired conductive network integrity, and reduced conductivity. The absence of hydroxylated carbon nanotubes reduced the hydrogen bonding interaction between the carbon nanotubes and the polyacrylonitrile matrix, weakening interfacial bonding. Poor interfacial bonding resulted in low stress transfer efficiency during fiber stretching, premature fracture due to localized stress concentration, and a slight decrease in breaking elongation. The reduced number of polar functional groups on the fabric surface slightly weakened its moisture adsorption capacity.

[0075] In Comparative Example 4, the synergistic dispersion effect among the carboxyl, amino, and hydroxyl groups was weakened when the three types of carbon nanotubes were blended in equal proportions. This resulted in partial agglomeration of the carbon nanotubes and a decrease in the connectivity of the conductive network. Uneven dispersion of the carbon nanotubes led to localized stress concentration, and the uneven interfacial interactions reduced the fiber's load-bearing capacity and tensile strength. Poorly dispersed carbon nanotubes acted as defect sources, inducing microcracks during stretching, reducing fiber ductility, and decreasing elongation at break. Changes in the functional group ratio affected surface polarity, but the overall change was not significant.

[0076] Comparative Example 5 changed the ratio of silver nanowires to copper nanoparticles to 1:1. The silver nanowires, with their high aspect ratio, can efficiently overlap to form long-range conductive pathways. While copper nanoparticles can fill the gaps between carbon nanotubes, copper has lower conductivity than silver, and its particle shape cannot replace the bridging effect of silver nanowires. With a reduced silver nanowire ratio, line-to-line contact in the conductive network decreases, contact resistance increases, and overall conductivity declines. The tensile strength is slightly lower than in Example 1; excess particles become stress concentration points, inducing microcracks during stretching and reducing strength. The elongation at break is lower than in Example 1; the increased proportion of rigid particles in the conductive filler limits fiber extensibility; simultaneously, the reduced silver nanowire ratio leads to decreased network slippage ability, making it unable to effectively disperse stress during deformation. The moisture regain is similar to that of Example 1.

[0077] Comparative Example 6 shows changes in silver wire size and copper particle diameter. Thicker silver wires result in a smaller specific surface area and a significantly lower density of wire-to-wire overlap points per unit mass. While increased length facilitates crossing greater distances, excessively long silver wires tend to agglomerate in the spinning solution, disrupting uniform dispersion. Larger copper particles cannot effectively fill the nanoscale gaps between carbon nanotubes, leading to numerous breaks in the conductive network and hindering electron transitions. Tensile strength is lower than in Example 1; large copper particles create significant defects in the fiber, becoming sources of crack initiation during stretching. The continuous support of the thicker silver wires to the fiber matrix is ​​weakened. Elongation at break decreases; excessively large particles impede the orientation and slippage of polyacrylonitrile molecular chains during stretching, increasing fiber brittleness and causing premature breakage.

[0078] Comparative Example 7, without the addition of ionic liquid, relies solely on electronic conductivity. The efficiency of the electronic conductivity network decreases and conductivity declines without the dispersion assistance of ionic liquid. Ionic liquid can act as a plasticizer to improve the flexibility of polyacrylonitrile molecular chains; its absence increases fiber rigidity but decreases toughness. Simultaneously, the cross-linked network lacks the regulation of ionic liquid, resulting in a slight decrease in strength. The lack of ionic liquid plasticizing effect restricts molecular chain movement, increasing fiber brittleness and decreasing elongation at break. The hydrophilic cations in the ionic liquid are key to improving moisture absorption; their absence significantly weakens the fabric's hydrophilicity, resulting in a marked decrease in moisture regain and deterioration in wearing comfort.

[0079] The overall effect of Comparative Example 8 is worse than that of Examples 1-3 of the present invention. It should be noted that there may be operational errors in the data of Comparative Example 8 and the results of CN110656391B, but this does not affect the comparative effect in the present invention.

[0080] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing an ionically conductive fabric for vital sign monitoring, characterized by, Includes the following steps: (1) Preparation of spinning solution: Polyacrylonitrile is dissolved in dimethylformamide to prepare a polymer solution, and stirred to dissolve, thus obtaining a two-component polyacrylonitrile spinning solution; (2) Preparation of carbon nanotube dispersion: Carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes were mixed, added to deionized water, and a dispersant was added. The mixture was then ultrasonically dispersed to obtain a carbon nanotube dispersion. (3) Preparation of composite conductive filler: Mix silver nanowires and copper nanoparticles to obtain conductive metal particles; add the conductive metal particles to the carbon nanotube dispersion prepared in step (2), continue ultrasonic dispersion, then centrifuge, wash and freeze dry to obtain composite conductive filler; (4) Compounding of ion-conductive finishing solution: The composite conductive filler, ionic liquid, waterborne polyurethane and crosslinking agent obtained in step (3) are added to the solvent, stirred and ultrasonically dispersed to obtain the ion-conductive finishing solution. (5) Blending electrospinning: The spinning solution from step (1) is mixed with the ion-conducting finishing solution from step (4), and injected into an electrospinning device for blending spinning to obtain a composite nanofiber membrane. (6) Thermal cross-linking and shaping: The composite nanofiber membrane obtained in step (5) is vacuum dried and heat-treated to obtain an ion-conductive fabric for vital sign monitoring.

2. The method of claim 1, wherein the ionically conductive fabric is prepared by the steps of: The polyacrylonitrile includes No. 1 polyacrylonitrile and No. 2 polyacrylonitrile; the average molecular weight Mw of No. 1 polyacrylonitrile is 80,000-90,000; the average molecular weight Mw of No. 2 polyacrylonitrile is 140,000-160,000.

3. The method for preparing the ion-conductive fabric for vital sign monitoring according to claim 2, characterized in that, The polyacrylonitrile includes No. 1 polyacrylonitrile and No. 2 polyacrylonitrile in a mass ratio of 1:(0.3-0.5).

4. The method for preparing the ion-conductive fabric for vital sign monitoring according to claim 1, characterized in that, The mass ratio of carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes is (45-55): (22-28): (22-28).

5. The method for preparing the ion-conductive fabric for vital sign monitoring according to claim 1, characterized in that, The dispersant is sodium dodecylbenzenesulfonate.

6. The method for preparing the ion-conductive fabric for vital sign monitoring according to claim 1, characterized in that, The silver nanowires and copper nanoparticles were mixed at a mass ratio of (13-15):(5-7).

7. The method for preparing the ion-conductive fabric for vital sign monitoring according to claim 6, characterized in that, The mass ratio of carbon nanotubes to conductive metal particles is (2-3):(1-1.5).

8. The method for preparing the ion-conductive fabric for vital sign monitoring according to claim 1, characterized in that, The mass ratio of the composite conductive filler, ionic liquid, waterborne polyurethane and crosslinking agent is (8-12):(12-18):(65-75):(2-4).

9. The method for preparing the ion-conductive fabric for vital sign monitoring according to claim 1, characterized in that, The diameter of the silver nanowires is 35-45 nm and the length is 12-18 μm; the particle size of the copper nanoparticles is 30-50 nm.

10. An ion-conductive fabric for vital sign monitoring prepared by the method according to any one of claims 1-9.

Citation Information

Patent Citations

  • A composite conductive fabric and its manufacturing method

    CN110656391B

  • Highly conductive fabric based on graphene conductive paste and its coating process

    CN113096850B